Marketing Communication of Indigenous People's Products Through Instagram Social Media @Gerainusantara_Aman - Umi Khoiriya; Ali Alamsyah Kusumadinata; Desi Hasbiyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Online marketing has increased drastically triggered by the implementation of Work from Home policies that limit offline marketing activities. Gerai Nusantara has also been using Instagram to increase the marketing of indigenous products. This study aims to conduct a SWOT analysis of Instagram social media @Gerainusantara_aman which is interesting as a marketing communication of indigenous people's products. The research method uses a descriptive qualitative approach through a SWOT analysis of internal factors (Weaknesses, Strengths) and external factors (Opportunities, Threats) from Instagram @Gerainusantara_aman. The results of this study show that Instagram @Gerainusantara_aman has a strength value smaller than the weakness value with a difference in value (-) 0.06, and an opportunity value smaller than the threat value with a difference in value (-) 0.08. The Instagram content posting strategy @Gerainusantara_aman is in the position of WT / Diversification strategy, which is to minimize existing weaknesses and avoid threats.